Practical Considerations and Recommendations for "a Revised Hippocratic Oath for the Era of Digital Health" - Rachele Hendricks-Sturrup; Maryam Nafie; Christine Lu (JMIR Publications, 2022)
The Hippocratic Oath (the "Oath") is a longstanding body of ethical tenets that have undergone several amendments to accommodate changes and evolutions in the practice of medicine. In their recent perspective entitled, "A Revised Hippocratic Oath for the Era of Digital Health," Meskó and Spiegel offered proposed amendments to the Oath to address both challenges and needs that follow digital health implementation in clinical practice. In this commentary, we offer additional thoughts and considerations to Meskó and Spiegel's proposed amendments to accomplish two goals: (1) reflect on the shared goals and values of all digital health stakeholders and (2) drive home the focus on affirming patient choice, autonomy, and respect.